Sponge Gourd Potential for the Raw Material of Paper and Dissolving Pulp - Nyoman J. Wistara; Yuhana Rahayu (Masyarakat Peneliti Kayu Indonesia, 2022)
Sponge gourd (Luffa cylindrica) provides a sustainable and cheap source of lignocellulosic materials potential for the raw material of paper and dissolving pulp. In the present works, sponge gourd fruits 5 and 8 months old were pre-hydrolyzed in an acidic (pH of 5) and neutral (pH of 7) at 165 C for 3 hours, and successively soda pulped at a maximum temperature of 170 oC for 4 hours with 20% active alkali. The resulting pulp was bleached by the D0E1D1E2D2 method. The bleached pulp was chemically analyzed to evaluate its feasibility for dissolving pulp based on the requirement of SNI 14-03-1989. The pulp feasibility for paper materials ware based on the measurement of fiber dimensions, fiber derivative values, and the strength properties of the pulp. It was found that the a-cellulose content of the sponge gourd coir was high compared to the requirement of SNI 14-03-1989. However, it did not satisfy the requirement of dissolving pulp due to its high extractives, ash, silica content, and low viscosity. The fiber of sponge gourd coir was classified into the quality class of II with intermediate pulp strength.